The positive outlook study- a randomised controlled trial evaluating the effectiveness of an online self-management program targeting psychosocial issues for men living with HIV: A study protocol - Millard, T.; Elliott, J.; Slavin, S.; McDonald, K.; Rowell, S.; Girdler, Sonya (BioMed Central Ltd, 2014)
Background: The emergence of HIV as a chronic condition means that people living with HIV are required to take more responsibility for the self-management of their condition, including making physical, emotional and social adjustments. This paper describes the design and evaluation of Positive Outlook, an online program aiming to enhance the self-management skills of gay men living with HIV. Methods/design. This study is designed as a randomised controlled trial in which men living with HIV in Australia will be assigned to either an intervention group or usual care control group. The intervention group will participate in the online group program 'Positive Outlook'. The program is based on self-efficacy theory and uses a self-management approach to enhance skills, confidence and abilities to manage the psychosocial issues associated with HIV in daily life. Participants will access the program for a minimum of 90 minutes per week over seven weeks. Primary outcomes are domain specific self-efficacy, HIV related quality of life, and outcomes of health education. Secondary outcomes include: depression, anxiety and stress; general health and quality of life; adjustment to HIV; and social support. Data collection will take place at baseline, completion of the intervention (or eight weeks post randomisation) and at 12 week follow-up. Discussion. Results of the Positive Outlook study will provide information regarding the effectiveness of online group programs improving health related outcomes for men living with HIV. Trial registration. ACTRN12612000642886.